Biocompatible and Highly Stretchable PVA/AgNWs Hydrogel Strain Sensors for Human Motion Detection. Issue 11 (6th September 2020) - Azadi, Shohreh; Peng, Shuhua; Moshizi, Sajad A.; Asadnia, Mohsen; Xu, Jiangtao; Park, Inkyu; Wang, Chun H.; Wu, Shuying
Abstract: Hydrogel‐based strain sensors have attracted considerable interest for applications such as skin‐like electronics for human motion detection, soft robotics, and human–machine interfaces. However, fabrication of hydrogel strain sensors with desirable mechanical and piezoresistive properties is still challenging. Herein, a biocompatible hydrogel sensor is presented, which is made of polyvinyl alcohol (PVA) nanocomposite with high stretchability up to 500% strain, high mechanical strength of 900 kPa, and electrical conductivity (1.85 S m ‐1 ) comparable to human skin. The hydrogel sensors demonstrate excellent linearity in the whole detection range and great durability under cyclic loading with low hysteresis of 7%. These excellent properties are believed to be contributed by a new bilayer structural design, i.e., a thin, conductive hybrid layer of PVA/silver nanowires (AgNWs) deposited on a pure strong PVA substrate. PVA solution of high concentration is used to fabricate the substrate while the top layer consists of dilute PVA solution so that high content of AgNWs can be dispersed to achieve high electrical conductivity. Together with a rapid response time (0.32 s) and biocompatibility, this new sensor offers great potential as a wearable sensor for epidermal sensing applications, e.g., detecting human joint and muscle movements. Abstract : This work demonstrates the fabrication of polyvinyl alcohol (PVA)‐based nanocomposite hydrogel strain sensors with a new bilayer design, i.e., a thin hybrid sensing layer is deposited on a pure PVA substrate. This design facilitates effective load transfer, and thereby resulting in excellent linearity, great durability, and low hysteresis, offering great potential as a wearable sensor for epidermal sensing applications.